Power transmissions : proceedings of the International Conference on Power Transmissions 2016 (ICPT 2016), Chongqing, P.R. China, 27-30 October 2016 /: proceedings of the International Conference on Power Transmissions 2016 (ICPT 2016), Chongqing, P.R. China, 27-30 October 2016. (2016) - Unknown
No abstract available